The Use of Financial Literacy for Growing Personal Finance - Ardi Gunardi; Mochammad Ridwan; Gugum Mukdas Sudarjah (Jurnal Keuangan dan Perbankan, 2017)
Financial literacy played an important role for everyone in managing personal finances. This research aimed to determine how the level of financial literacy in students S1 Faculty of Economics and Business, Universitas Pasundan and investigate what factors are influencing it. The observed respondents were students from the Faculty of Economics and business, Universitas Pasundan. The research data was collected through questionnaires, descriptive analysis, and test multinomial logit. Based on the results of the research showed that the level of financial literacy from undergraduate students UniversitasPasundan was in a low category. Financial literacy was determined by gender, GreaterAcademic Achievement (GPA), parental education level, and parental income level, whereas for age, year of study and residence do not contribute to the research model. The results of this study were expected to support the personal financial planning of students in improving the skills of reading, analyzing, and managing their own finances, thus avoiding the daily financial problems.DOI: https://doi.org/10.26905/jkdp.v21i3.1489